2016
DOI: 10.1249/mss.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Metaboreflex on Pulmonary Vascular Capacitance in Heart Failure

Abstract: Purpose An impaired metaboreflex is associated with abnormal ventilatory and peripheral vascular function in heart failure (HF), whereas its influence on cardiac function or pulmonary vascular pressure remain unclear. We aimed to assess whether metabolite-sensitive neural feedback (metaboreflex) from locomotor muscles via post-exercise regional circulatory occlusion (RCO) attenuates pulmonary vascular capacitance (GXCAP) and/or circulatory power (CircP) in HF patients. Methods Eleven HF patients (NYHA class:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…Irrespective of augmented or blunted sympathetic responses to metaboreflex activation, most studies show a preserved BP increase to metaboreflex activation in HF (12,27,122,132). However, as previously reported in animal studies, HF individuals have an impaired capacity to increase SV and CO H95 during metaboreflex activation; thus the metaboreflex-mediated BP increase is largely dependent upon an increase in SVR (12,27,122,132,165). Accentuated peripheral vasoconstriction occurs in nonactive vascular beds (122) and in active muscle (3), with the latter reducing skeletal muscle perfusion during exercise, thereby increasing fatigue-related symptoms and stimulating further metaboreflex responses.…”
Section: Studies In Humansmentioning
confidence: 86%
See 1 more Smart Citation
“…Irrespective of augmented or blunted sympathetic responses to metaboreflex activation, most studies show a preserved BP increase to metaboreflex activation in HF (12,27,122,132). However, as previously reported in animal studies, HF individuals have an impaired capacity to increase SV and CO H95 during metaboreflex activation; thus the metaboreflex-mediated BP increase is largely dependent upon an increase in SVR (12,27,122,132,165). Accentuated peripheral vasoconstriction occurs in nonactive vascular beds (122) and in active muscle (3), with the latter reducing skeletal muscle perfusion during exercise, thereby increasing fatigue-related symptoms and stimulating further metaboreflex responses.…”
Section: Studies In Humansmentioning
confidence: 86%
“…HF patients also suffer with exertional dyspnea, which might be related to changes in pulmonary vascular dynamics (83,165), which is an important mediator of exercise intolerance in this population (31). Importantly, activation of the metaboreflex may promote pulmonary vasoconstriction (83,165) and abnormal ventilatory responses during exercise in HF (122,123,126,144,145). Piepoli et al (122) reported increased ventilatory responses during PEMI after leg cycling exercise in patients with HF.…”
Section: Studies In Humansmentioning
confidence: 99%
“…In contrast, but while still physiologically linked to peripheral-central hemodynamic maldistribution, noteworthy discussions spanning across study lines of slowed V O 2 kinetics (both pulmonary and muscle) to abnormal activation of group III/IV afferents commonly implicate the milieu of the blood biochemical intramuscular environment (20,(22)(23)(24)50) as a key factor preceding the cascade of events leading to exercise intolerance in HF (1,28,31,37,39,42). For example, it has been suggested by Scott et al (39,40), Crisafulli et al (11), our group (31,44), and others (1,35) that skeletal muscle phenotypes, particularly those associated with provoking recruitment of nonoxidative energetic demands (leading to, e.g., increased H ϩ , increased P i /phosphocreatine, and increased La Ϫ ) prime an intramuscular environment ideal for group III/IV afferent activation, resulting in exercise intolerance secondary to augmented SVR, blood pressure, and ventilation in HF. Likewise, there are well-established parallels between prolonged V O 2 kinetics and increased O 2 def coinciding with skeletal muscle characteristics that include unfavorable contributions from 1 type IIb fiber (glycolytic) recruitment/proportion, increased H ϩ , and increased P i /phosphocreatine in potentially explaining the predisposition for exercise intolerance in HF (5,7,18,25,28,36,37,42).…”
Section: Discussionmentioning
confidence: 99%
“…This is a scientific area requiring directed efforts focusing on both mechanistic and patient-oriented clinical research, possibly centering on afferent pathways involving exercise-induced neuromuscular signaling changes. Examples of such phenomena have been frequently tested and observed in HFrEF [30,31,[37][38][39][40][41][42][43]. In this context, many cases of refractory hypertension are suggested to be the result of excess and dysregulated sympathetic tone [6].…”
Section: Exercise and Physical Activitymentioning
confidence: 99%